Pengaruh Tindakan Bullying Terhadap Perkembangan Mental Anak Kelas V SDN 122365 Pematangsiantar 2024 - Sitohang, Josua D; Tambunan, Jubelando O. (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
This study examines the effect of bullying on children's mental development in class V of SDN 12365 Pematangsiantar. Researchers used a quantitative approach with a sample of 23 students. To measure the strength of the linear relationship between two variables with normal data distribution, Pearson Correlation Product Moment analysis was used with the help of SPSS 21. The results showed that bullying has a positive and significant correlation with students' mental development, with a correlation coefficient of 0.657. The calculated value for the bullying variable (5.783) is also greater than the table value, which corresponds to the significance level (0.000). This finding indicates that bullying behavior has a significant positive impact on mental development, showing how bullying affects students' mental state. The coefficient of determination (r²) of 0.432 indicates that bullying behavior affects about 43.2% of mental development, while other factors account for 48.5% in students' mental formation.